Properties of particleboard from wild acacia mangium: effect of particle size and board thicknesss / Siti Hazimah Awal Ud-Din - Awal Ud-Din, Siti Hazimah (2013)
The purpose of this study was to determine the effect of particle size and board thickness on the mechanical properties (Modulus of Elasticity, Modulus of Rupture, and Internal Bond) and physical properties (thickness swelling and water absorption) of Acacia mangium particleboard. The particle sizes used were O.5mm, 1.0mm and 2.0mm, while board thickness used were 6mm and 12mm. Each of the size was mixed with phenol formaldehyde resin with concentration 9%. The results showed that no significant effect in MOE and MOR was observed when particle size was increased. It also show, as the particle size increased, the particleboard's mechanical and physical properties increased. Meanwhile, mechanical properties (MOE and MOR) show an increment on thick board compared thin board and physical properties (WA and TS) show higher absorption of water when higher board thickness. Overall results showed that particleboard made from Acacia mangium for mechanical properties met the minimum Malaysian Standard requirement, but the physical properties for a board made of 2.0mm particle size at 12mm thickness exceed minimum standards. Thus, higher board thickness and large particle size gave better mechanical properties (MOE & MOR). IB strength increased by decreasing of particle size and reducing board thickness.